Aroma therapy in the learning process improves students' focus and memory - Aprianti, Nurul Annisa (Asian Journal of Multidisciplinary Research, 2025)
Aroma therapy has been widely used in a variety of fields, including health and psychology, due to its effects in improving mental and cognitive well-being. In the context of education, aroma therapy has great potential in helping students improve focus and memory during the learning process. Some studies suggest that certain scents, such as peppermint and rosemary, can stimulate the central nervous system and improve cognitive functions related to attention and memory retention. However, despite the overwhelming scientific evidence supporting the benefits of aroma therapy, its use in the education system is still limited. This study aims to analyze the impact of aroma therapy in improving students' focus and memory in the learning process. The method used is a literature study with a qualitative approach, which reviews various previous studies on the effects of essential oils on cognitive performance. Data was collected from a variety of academic sources, including scientific journals, conference proceedings, and relevant research reports in the last five years. The results of the study showed that aroma therapy, especially through the inhalation of essential oils such as peppermint, rosemary, and lavender, can improve focus, reduce anxiety, and improve students' memory retention. This effect is associated with stimulation of the limbic system and increased activity of neurotransmitters that play a role in brain performance. Thus, aroma therapy can be an additional method that can be integrated in the learning environment to increase the effectiveness of students' learning.